Heterogeneity between and within Strains of Lactobacillus brevis Exposed to Beer Compounds - Zhao, Yu; Knøchel, Susanne; Siegumfeldt, Henrik (Frontiers in Microbiology, 2017)
This study attempted to investigate the physiological response of six L. brevis strains to hop stress, with and without the addition of Mn2+ or ethanol at the single cell level using fluorescence microscopy and flow cytometry. The combined approach was faster than the traditional colony based method, but also provided additional information about population heterogeneity with regard to membrane damage and cell size reduction, when exposed to hop compounds. Different physiological subpopulations were detected under hop stress in both hop tolerant and sensitive strains. A large proportion of cells were killed in all the tested strains, but a small subpopulation from the hop tolerant strains eventually recovered as revealed by pHi measurements. Furthermore, a short term protection against hop compounds was obtained for both hop tolerant and sensitive strains, by addition of high concentration of Mn2+. Addition of ethanol in combination with hop compounds caused an additional short term increase in damaged subpopulation, but the subsequent growth suggested that the presence of ethanol provides a slight cross resistance towards hop compounds.